A Phase 2a Trial Investigating the Safety and Tolerability of the Novel Cortical Enhancer IRL752 in Parkinson's Disease Dementia. Issue 6 (21st March 2020) - Svenningsson, Per; Odin, Per; Dizdar, Nil; Johansson, Anders; Grigoriou, Sotirios; Tsitsi, Panagiota; Wictorin, Klas; Bergquist, Filip; Nyholm, Dag; Rinne, Juha; Hansson, Fredrik; Sonesson, Clas; et al.
Abstract: Background: IRL752 is a novel small‐molecule compound that acts to regioselectively enhance norepinephrine, dopamine, and acetylcholine neurotransmission in the cerebral cortex. Objective: The primary objective of the trial was to investigate the safety and tolerability of IRL752 in patients with Parkinson's disease and dementia. Methods: Patients with Parkinson's disease and dementia were randomized to IRL752 or placebo treatment (3:1 ratio) for 28 days. The study drug was given as an adjunct treatment to the patients' regular stable antiparkinsonian medication. Dosing was individually titrated for 14 days after which the dose was kept stable for an additional 14 days. Results: A total of 32 patients were randomized to treatment, and 29 patients completed the 4‐week treatment. Adverse events were generally mild and transient and were mostly reported during the dose titration phase. There were 2 serious adverse events, and none of them were related to the experimental treatment. The average dose achieved in the stable dose phase was 600 mg daily, yielding a 2‐hour postdose plasma concentration of about 4 μM on day 28. Exploratory assessment of secondary outcomes indicated efficacy for symptoms and signs known to be poorly responsive to levodopa. Conclusions: IRL752 appears to be safe and well tolerated for a 4‐week treatment in patients with Parkinson's disease and dementia. © 2020 International Parkinson and Movement Disorder Society